Phase transformations in the reaction cell of TiNi-based sintered systems. (16th May 2018) - Artyukhova, Nadezhda; Anikeev, Sergey; Yasenchuk, Yuriy; Chekalkin, Timofey; Gunther, Victor; Kaftaranova, Maria; Kang, Ji-Hoon; Kim, Ji-Soon
Abstract: The present work addresses the structural-phase state changes of porous TiNi-based compounds fabricated by reaction sintering (RS) of Ti and Ni powders with Co, Mo, and no additives introduced. The study also emphasizes the features of a reaction cell (RC) during the transition from the solid- to liquid-phase sintering. Mechanisms of phase transformations occurring in the solid phase, involving the low-melting Ti2 Ni phase within the RC, have been highlighted. Also, the intermediate Ti2 Ni phase had a crucial role to provide both the required RS behavior and modified phase composition of RS samples, and besides, it is found to be responsible for the near-equiatomic TiNi saturation of the melt. Both cobalt and molybdenum additives are shown to cause additional structuring of the transition zone (TZ) at the Ti2 Ni−TiNi interface and broadening of this zone. The impact of Co and Mo on the Ti2 Ni phase is evident through fissuring of this phase layer, which is referred to solidified stresses increased in the layer due to post-alloying defects in the structure.